POLA ATTACHMENT TERHADAP ORANG TUA DAN KAITANNYA DENGAN TENDENSI AGRESI PADA SISWA PELAKU SCHOOL BULLYING DI SMU JAKARTA - Eunike Sri Tyas Suci; Teresia Maria Hilda (MANASA, 2012)
School bullying is a serious problem in Indonesia and need the attention of scholars from different knowledge background to find the solution. It involves aggressive behavior which is considered as normal among young people. Their behaviour is highly influenced by the school condition and their peer group developed at the early childhood in the family. The types of attachment with parents may result in a certain child behavior, as children learn from what their parents do at home. There are three types of attachment styles. i.e. secure, avoidance, and ambivalence attachment styles. This research attempts toexamine the relationship between childhood attachment style and the tendency of aggression from the bully’s perspective. Using quantitative approach, the study population was students considered as bullies in Jakarta high schools. Sample taken from two selected schools known as having problems with bullying in Jakarta. The sampling technique was stratified random sampling. The study used the adapted Attachment Styles Questionnaire to measure the attachment style of students, and The Tendency of Aggression for School Aged Children Questionnaire. The total respondents were 53 students ranged between 15 to 18 years old. One interesting finding is the fact that most respondents were female (n=35, 66%). This is different from our previous assumption that bullies commonly are males. It might be true as the indicators of bullying which were reported mostly were verbal. Another finding is that 43 respondents had secure attachment style, and there was no relationship between such attachment style with the tendency of aggression (r = 0,151; p > .05). Due to the small number on the other two groups, the research was unable to do the analysis. Future study needs to be done with these two groups, as it is likely that non-secure attachment styles relate to the aggression behaviour.